IMPROVING THE STUDENTS’ SPEAKING ACHIEVEMENT BY APPLYING THE STUDENTS TEAM ACHIEVEMENT DIVISION AT CLASS XI MIA 2 OF SMA NEGERI 6 MEDAN - Resty Wahyuni (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2022)
This study aims to improve the ability to speak English in students in Medan. In this study, research data collection techniques used observation, interviews and documentation methods. The data sources for this study were students at SMA Negeri 6 Medan in class XI MIA2. By applying the Student Team Achievement Division learning model and using dialogue media. the research instrument is test, observation sheet, interview (Classroom Acton Research) . This study uses a qualitative and quantitative design. The research data analysis technique uses three steps, namely 1. Data reduction, 2. Data presentation, 3. Making conclusions. Findings from data analysis, Before applying the Studnet Team Achievement Division (STAD) learning model, there were 30 students (96%) who did not complete with a score of 44.46-66.67. and 6 (4%) students 78.78 - 88.89 completed with grades. And after applying the Student Team Achievement Division (STAD) learning model, in the first cycle there were 35 students (99%) who scored 78.78. 88.89 this value has exceeded the KKM score of 75% and 1 student (1%) did not complete. There was an increase of 26.15. The conclusion is that the application of the Student Team Achievement Division learning model is very effective in improving students' speaking skills.